Effects of a coach-guided videoconferencing acceptance and commitment therapy intervention combined with psychoeducation on distressed individuals living with spinal cord injury: a preliminary mixed-methods study. Issue 4 (13th February 2023) - Han, Areum; Wilroy, Jereme D.; Jenkins, Jeremy; Yuen, Hon K.
Abstract: Purpose: This study examined effects of coach-guided videoconferencing acceptance and commitment therapy (ACT) accompanied by psychoeducation on distressed individuals with spinal cord injury (SCI) and explored participants' experiences in the intervention. Materials and methods: Ten people with SCI participated in 8 individual videoconferencing sessions delivered by trained coaches. Data using self-reported questionnaires and individual interviews was collected at pretest and posttest and analyzing using Wilcoxon signed-rank tests and interpretative phenomenological analysis (ClinicalTrials.gov ID: NCT04670406). Results: Statistically significant improvements were found in depression, anxiety, stress, grief, engagement in meaningful activities, and self-compassion with medium to large effect sizes. There was no significant change in quality of life, resilience, and ACT processes. Participants gained a new way of thinking by: being aware of thoughts and emotions; exploring perceptions of others; and focusing on the present. Also, the intervention equipped participants to deal with challenges by: improving coping with SCI-related conditions; practicing self-compassion, acceptance, and meditation; and acquiring skills of value-based decision making and committed action. Conclusions: Findings contribute to the limited evidence as the first study that measured effects of videoconferencing ACT on people with SCI. Future randomized controlled trials are needed to measure efficacy of internet-delivered ACT for people with SCI. IMPLICATIONS FOR REHABILITATION: Guided videoconferencing ACT may reduce depressive symptoms, anxiety, stress, and grief and increase engagement in meaningful activities and self-compassion in people with SCI. Professionals may consider ACT as a supportive or adjunct service for people with SCI who experience psychological distress.